OVERVIEW ON THE Re-Os ISOTOPIC METHOD AND ITS APPLICATION ON ORE DEPOSITS AND ORGANIC-RICH ROCKs - Marques, Juliana Charão (Geochimica Brasiliensis, 2013)
The Re-Os method has in the last twenty years experienced outstanding improvements and is now widely applied in earth science studies. The unique geochemical characteristics of the isotopic pair allow its application on investigations that vary from cosmochemistry and mantle-crust interactions to weathering and seawater composition. Re-Os has proved to be a valuable geochronometer for mineral deposits owing its chalcophile and siderophile nature that allow direct dating of ore minerals. Moreover, Re-Os isotopic system can provide not only ages for organic-rich sedimentary clastic rocks and oil migration, but also fingerprints the sources of Os inputs to seawater. In this paper, an overview of the method and its main applications is provided with emphasis on geochronology, showing whenever possible Brazilian examples, and providing a wide variety of selected references for those who are interested in greater detail.